No Righteous Man Is a Frog: Resemblance as a Hermeneutical Problem (Circe de clásicos y modernos, 2025)
The equivocality of the term “resemblance” gives rise to an inconclusive dialogue between Celsus and Origen. While the latter foregrounds the risks of misinterpreting biblical texts, replete with hidden meanings that escape unwary eyes, Celsus remains insensitive to the subtleties of biblical textuality, even as he promotes allegorical interpretation in an attempt to salvage sometimes impious stories, such as those from the epic tradition, which dare to attribute extremely vile actions to divinities. Origen appeals to Philo’s authority on hermeneutics to defuse pagan attacks on the Christian doctrine of the creation of man in the image and likeness of God.
Keywords: Origen; Celsus; resemblance; creation; hermeneutics